The Role of von Willebrand Factor Antigen in Predicting Survival of Patients with HBV-Related Cirrhosis - Youmin Pan; Renyong Guo; Yan Lv; Dawei Cui; Jue Xie (Canadian Journal of Gastroenterology and Hepatology)
Objective. The model for end-stage liver disease (MELD) scoring system cannot be used to assess the deterioration of patients with liver cirrhosis caused by infection and portal hypertension. Elevated von Willebrand factor antigen (vWF-Ag) in plasma is associated with portal pressure and complications in patients with liver cirrhosis. We aimed to evaluate whether the addition of vWF-Ag can improve the risk prediction ability of the MELD scoring system. Methods. A total of 228 patients with hepatitis B virus (HBV)-related liver cirrhosis were eligible for inclusion in this retrospective study. The vWF-Ag level was assessed by enzyme-linked immunosorbent assay (ELISA). The endpoint of this study was defined as the time to liver transplantation or death. Univariate and multivariate analyses were performed to assess the risk factors associated with transplant-free mortality. Receiver operating characteristic (ROC) curve analysis was used to assess potential discriminatory variables for transplant-free mortality. Results. During a median follow-up interval of 30.23 months, 124 patients (54.4%) reached the endpoint of this study. Patients who died or underwent liver transplantation had elevated levels of MELD and vWF-Ag. Moreover, vWF-Ag and MELD showed comparable predictive potential for transplant-free survival (area under the curve [AUC], vWF-Ag = 0.71; AUC, MELD = 0.73). Ultimately, vWF-Ag can significantly improve the predictive potential of MELD in determining transplant-free mortality (AUC, MELD-vWF-Ag = 0.79, P = 0.006). Conclusion. An elevated vWF-Ag level was independently associated with transplant-free mortality in patients with liver cirrhosis. The inclusion of vWF-Ag in the MELD scoring system can improve mortality predictions in patients with liver cirrhosis.